Asymmetric aerobic oxidation of secondary alcohols catalyzed by poly(N-vinyl-2-pyrrolidone)-stabilized gold clusters modified with cyclodextrin derivatives. Issue 100 (15th November 2019) - Hirano, Koto; Takano, Shinjiro; Tsukuda, Tatsuya
Abstract : Surface modification of poly( N -vinyl-2-pyrrolidone)-stabilized gold clusters (1.8 ± 0.6 nm) with aminated cyclodextrins induced aerobic oxidative kinetic resolution of racemic secondary alcohols ( k rel = 1.2). Abstract : Surface modification of poly( N -vinyl-2-pyrrolidone)-stabilized gold clusters (1.8 ± 0.6 nm) with aminated cyclodextrins induced aerobic oxidative kinetic resolution of racemic secondary alcohols ( k rel = 1.2).